PENINGKATAN KUALITAS PENDIDIKAN DAN PEMBANGUNAN KULTUR GLOBAL - Umar, Jusnimar (Universitas Islam Negeri Raden Intan Lampung, 2015)
THE QUALITY IMPROVEMENT OF EDUCATION AND DEVELOPMENT OF GLOBAL CULTURE: The main problem that must be answer is how is the Education Quality Improvement and Development of Global Culture? The author examined the point of the study related to the education to understand the effort to prepare the learner; improving the quality of education through teaching, guidance and training with basic cultural education institution or formal education in in the era of globalization; and the development of global culture. This article found that the education will fulfill the kids and adults using cultural background to understand the changing happened. They must be able to choose the information and interpret and place the things happened in the global culture perspective. In the other side, we have given the big knowledge, but in the other side, we remove and ignore the value of attitudes and behavior, cognitive, and affective and psychomotor aspects. The effect of globalization makes us aware that the global culture may be removed the self- identity and the culture identity. In fact, both identities are the milestones to contribute the development of global culture.